Racially Restrictive Covenants: The Making of All-White Suburbs in Milwaukee County - (:unkn) unknown (My University, 1979)
Migration of African American families to developing suburban areas in the Milwaukee metropolitan area was inhibited by both governmental actions and private discrimination. A study by Lois Quinn of the Metropolitan Integration Research Center in 1979 found racially restrictive covenants operating in at least sixteen of the eighteen Milwaukee County suburbs. Subdivisions established in 1927, for example, in Cudahy, Shorewood, West Milwaukee, Whitefish Bay and Wauwatosa excluded all non-Caucasian families. In the 1930's subdivisions created in Bayside, Fox Point, Glendale, Greenfield, Hales Corners, St. Francis and West Allis were still using covenants to exclude African Americans. As late as 1958, ten years after the U.S. Supreme Court outlawed judicial Supreme Court outlawed judicial enforcement of these covenants, race restrictions were recorded for a new subdivision in Greendale. A case study of Wauwatosa, an attractive middle class suburb less than 5 miles from the black ghetto, revealed that 51 subdivisions (covering 1/3 of all residential land in the community) were developed with restrictive covenants which prevented non-Caucasians from purchasing or renting homes in their neighborhoods.
Keywords: racial segregation; discrimination; housing covenants